Farewell to the Past Century? - Bartosz Hordecki (Ksiegarnia Akademicka Publishing, 2019)
The Russian authorities, supported by the representatives of the Russian cultural circles, celebrated 2018 as a year of harmonious reception of their literary traditions. Accordingly, the 100th anniversary of Alexander Solzhenitsyn’s birth was included into the series of commemorations and jubilees, minimizing, however, the problem of the Russian literature’s profound heterogeneity and inconsistency. Disregarding differences between literary currents, equalizing various, often contradictory intellectual phenomena can manifest that the Russian authorities search for a kind of cultural synthesis which will become a solid foundation of the Russianness in the XXI century. Nevertheless, their integrative ambitions are some how static or demobilizing. Moreover, these seem to be based on the conviction that cultural policy is not about determining and enhancing directions of further literary development but about assimilating and even restricting various artistic forces and traditions.